Evaluation of diaphragm in penetrating left thoracoabdominal stab injuries: The role of multislice computed tomography. Issue 9 (September 2015) - Yucel, Metin; Bas, Gurhan; Kulalı, Fatma; Unal, Ethem; Ozpek, Adnan; Basak, Fatih; Sisik, Abdullah; Acar, Aylin; Alimoglu, Orhan
Abstract Introduction Penetrating left thoracoabdominal stab injuries are accompanied by diaphragmatic injury in 25–30% of cases, about 30% of which later develop into diaphragmatic hernia. This study aimed to determine the role of multislice computed tomography in the evaluation of left diaphragm in patients with penetrating left thoracoabdominal stab wounds. Materials and methods This study reviewed penetrating left thoracoabdominal stab injuries managed in our clinic between April 2009 and September 2014. The thoracoabdominal region was defined as the region between the sternum, fourth intercostal space, and arcus costa anteriorly and the vertebra, lower tip of scapula, and the curve of the last rib posteriorly. Unstable cases and cases with signs of peritonitis were operated with laparotomy; the remaining patients were closely monitored. Forty-eight hours later, a diagnostic laparoscopy was applied to evaluate the left hemidiaphragma in asymptomatic patients who did not need laparotomy. The preoperatively obtained multislice thoracoabdominal computed tomography images were retrospectively examined for the presence of left diaphragm injury. Then, operative and tomographic findings were compared. Results This study included a total of 43 patients, 39 (91%) males and 4 (9%) females of mean age 30 years (range 15–61 years). Thirty patients had normal tomography results, whereas 13 had left diaphragmatic injuries. An injury to the left diaphragm was detected during the operation in 9 (1 in laparotomy and 8 in diagnostic laparoscopy) of 13 patients with positive tomography for left diaphragmatic injury and 2 (in diagnostic laparoscopy) of 30 patients with negative tomography. Multislice tomography had a sensitivity of 82% (95% CI: 48–98%), a specificity of 88% (71–96%), a positive predictive value of 69% (39–91%), and a negative predictive value of 93% (78–99%) for detection of diaphragmatic injury in penetrating left thoracoabdominal stab injury. Conclusions Although diagnostic laparoscopy is the gold standard for diaphragmatic examination in patients with penetrating left thoracoabdominal stab wounds, multislice computed tomography is also valuable for detecting diaphragmatic injury.